O USO DE VIDEOGAMES COMO TEXTOS NAS AULAS DE LÍNGUA INGLESA: CONTRIBUIÇÕES DOS ESTUDOS DOS LETRAMENTOS E DA ABORDAGEM MULTIMODAL - Borges, Célia Nunes Pereira (2021)
The use of video games is present in the everyday life of people of different age groups and also in the school context through technologies such as cell phones. Aiming at associating activities through this digital media and foreign language teaching, this research investigated the interaction through reading and the contributions that platform games can provide to students during the English teaching-learning process. Considering the new theories of literacy and new semiotic domains, the research was carried out in a collaborative and reflexive way among the participants through the application of the games, the observation of the phases and the register of the new knowledge in English language during the execution of the project. Under the contributions of Kress (2010), Cope, Kalantzis (2008, 2009), New London Group (1996, 2000), Gee (2003, 2005, 2007), Pérez-Latorre et al. (2016) and Machin (2007) we approach the formation of the individual open to new knowledge, especially technological knowledge, in the context of the classroom and anchor ourselves in the analytical dimensions: Ludo-narrative dimension (Ludo-narrative dimension) and System-gameplay dimension (system-gameplay dimension). Using the research methodology in a collaborative and qualitative approach, the results point to the interaction of the participants through the game as a pedagogical tool, dialoguing with other semiotic interfaces, interacting through reading in the English language seeking to create a more critical and reflexive posture.